![image](https://tex.z-dn.net/?f=+%5Csqrt%7Bx%2B1%7D%3E%5Csqrt%5B3%5D%7B3x-1%7D%5C%5C%0A%5Csqrt%7Bx%2B1%7D%3Dt%5C%5C%0A%5Csqrt%5B3%5D%7B3x-1%7D%3D%5Csqrt%5B3%5D%7B3t%5E2-4%7D%5C%5C%0A)
\sqrt[3]{3x-1}\\
\sqrt{x+1}=t\\
\sqrt[3]{3x-1}=\sqrt[3]{3t^2-4}\\
" alt=" \sqrt{x+1}>\sqrt[3]{3x-1}\\
\sqrt{x+1}=t\\
\sqrt[3]{3x-1}=\sqrt[3]{3t^2-4}\\
" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+++t%3E%5Csqrt%5B3%5D%7B3t%5E2-4%7D%5C%5C%0A+t%5E3%3E3t%5E2-4%5C%5C%0At%5E3-3t%5E2%2B4%3E0%5C%5C%0A+%28t-2%29%5E2%28t%2B1%29%3E0%5C%5C%0A%28-1%3B2%29+%5C+U+%5C+%282%3B%2Boo%29%5C%5C%0A%5C%5C%0A)
\sqrt[3]{3t^2-4}\\
t^3>3t^2-4\\
t^3-3t^2+4>0\\
(t-2)^2(t+1)>0\\
(-1;2) \ U \ (2;+oo)\\
\\
" alt=" t>\sqrt[3]{3t^2-4}\\
t^3>3t^2-4\\
t^3-3t^2+4>0\\
(t-2)^2(t+1)>0\\
(-1;2) \ U \ (2;+oo)\\
\\
" align="absmiddle" class="latex-formula"> теперь ставя заместо
![x+1 x+1](https://tex.z-dn.net/?f=x%2B1)
и учитывая ОДЗ
получаем